On the precarious path of reverse neuro-engineering - Marom, Shimon; Meir, Ron; Braun, Erez; Gal, Asaf; Kermany, Einat; Eytan, Danny (Frontiers in Computational Neuroscience, 2009)
In this perspective we provide an example for the limits of reverse engineering in neuroscience. We demonstrate that application of reverse engineering to the study of the design principle of a functional neuro-system with a known mechanism, may result in a perfectly valid but wrong induction of the system's design principle. If in the very simple setup we bring here (static environment, primitive task and practically unlimited access to every piece of relevant information), it is difficult to induce a design principle, what are our chances of exposing biological design principles when more realistic conditions are examined− Implications to the way we do Biology are discussed.